Transient liquid phase (tlp) diffusion bonding of Ti45Ni49Cu6 P/M components using Cu interlayer - Kejanli, Haluk; Taskin, Mustafa; Kolukisa, Sedat; Topuz, Polat (Springer London Ltd, 2009)
In this study, transient liquid phase diffusion bonding parameters of Ti45Ni49Cu6 P/M components using copper interlayer were experimentally investigated in a protective (argon) atmosphere. Bonding processes of sintered Ti45Ni49Cu6 P/M compacts were carried out at various temperatures and bonding periods while bonding pressure was kept unchanged. The process pressure, 20 MPa, was selected just below those which would cause macro deformations. Optical microscopy, scanning electron microscopy, and energy dispersive spectroscopy were employed for microstructure examinations. Shear strength and hardness (HB) of bonded specimens were measured at bond interface and parent materials for mechanical property evaluations. Along the bond interface, copper, titanium, and nickel atom mutual migration was observed. Structural tests, metallographic analysis have shown the integrity of the diffusion bonded hardware, bonded between 940 and 970A degrees C process temperatures, for 40-60-min bonding periods.
Keywords: Diffusion bonding; Ti Ni Cu powder metallurgy component; TLP; Copper interlayer